(untitled) (Revista de Artes Marciales Asiáticas, 2022)
The aim of this paper was to quantify the advantage granted to seeds in the case of professional judo knockout competitions. We used Monte-Carlo simulations to compute statistics including the probability of winning the competition, reaching the final or winning a medal in a standard draw compared to a random draw. We showed that the advantage given to seeds is often significant. As a result, misclassification in the ranking list is at a great disadvantage for top athletes that are not seeded. Interestingly, the advantage given to seeds appears robust as a function of parameters, such as sex or number of athletes, and modelling assumptions. Simulation is a flexible tool for athletes to take decisions in managing their position in the ranking list and to optimize their probability of success in major events.